Career Development in Knowledge Management. Issue 1 (13th October 2021) - Allen, Jeff; An, Lu; Hofman, Darra; Islam, Anwarul; Pfeiffer, Heather D.
Abstract: This is a SIG‐KM sponsored panel presented by members of the SIG‐KM officer team. First, the panel will overview their experience in knowledge management (KM) as scholars and scholar‐practitioners. They will briefly discuss their career development successes and hurdles as a roadmap for others to follow. Second, the panel will discuss career pathways for KM scholars and scholar‐practitioners in a global knowledge economy. Finally, they will hold an open discussion with audience members to share their experiences, expectations and hopes for the KM and the broader field of information science. [90 minute session].